(untitled) (Docentes 2.0 Journal, 2016)
This statement is reinforced by the conclusions presented by Dr. Diana Oblinger (2005) who states that there has been a change in the relationship students have with technology. The students to which his study refers are those belonging to the Net generation, who are all those born after 1982. These students have had throughout their life intense contact with technology, which has caused it to be seen as intrinsic part of their lives.